Views of the Government and Plan of Action on the Recommendations of the National Transport Policy Committee, May 1982 - Planning Commission (Planning Commission, 1982)
This document summarizes the Government of India’s response to the National Transport Policy Committee (NTPC) recommendations of May 1982, outlining a comprehensive action plan for strengthening the country’s transport system. The response emphasizes long-term capacity planning, realistic demand forecasting, and improved passenger and rural transport services. Key policy directions include intermodal integration, rationalization of subsidies, cost-reflective pricing, and enhanced investment in railways, roads, ports, and pipelines. The proposal to establish a National Transport Commission underscores the importance of coordinated oversight and environmental considerations. Complemented by a broader framework for inter-ministerial and state-level coordination, the document presents a structured approach to transport and infrastructure governance aimed at promoting efficiency, balanced regional development, and sustainable economic growth in India.
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Keywords: National Transport Policy Committee; Transport Policy Reform; Infrastructure Development; Transport Capacity Planning; Intermodal Integration; Demand Forecasting; Subsidy Rationalization; National Transport Commission; Government Coordination; Sustainable Transport Planning